Potential productivity of Arundo donax in two contrasting environments from medium-term experiments. Issue 13 (10th November 2023) - Sulas, Leonardo; Deligios, Paola A.; Cossu, Marco; Ledda, Luigi; Re, Giovanni A.; Sanna, Federico; Tiloca, Maria Teresa; Urracci, Giulia Roberta; Virdis, Adriana
ABSTRACT: Marginal land exploitation devoted to versatile crops, such as giant reed, is related to the degree of land marginality. Two experiments were conducted in two sites of Sardinia (Italy) to investigate the effects of management on dry matter yield and water productivity (WP). Experiment 1 compared four crop evapotranspiration restoring treatments (100%, 75%, 50%, 25%, and a rainfed control) over 5 years. Experiment 2 lasted 7 years and investigated zero-input supply on crop response. Experiment 1, notwithstanding well-watered conditions (Irr100), showed a higher value of biomass production during the last year monitored, but yielding only 13.5 Mg DM ha −1 and with no significant difference from Irr75. Moreover, being equal the average dry matter yield, in the Irr100, we would save 3630 m 3 of irrigation water by achieving the same WP recorded in the Irr25 (25% ETc restoring). Experiment 2, being equal rainfall amount, raised WP values that picked 8.2 kg m −3 during 2018. Results indicate that in less favourable soils as the Experiment 1, well-watered conditions do not ensure better crop growth and productivity, whereas in deep soils (Experiment 2) promising productive results, as well as ecosystem services, could be obtained without any input supply.